Progress on Tai Chi Therapy for Patients with Senile Knee Osteoarthritis - kun HU; Meiqin LIN; Jiao LIU; Dalu QI; Jia HUANG (康复学报)
As a kind of physical and mental coordination of movement, Tai Chi can excercise both internal and external, coordinate internal organ functions, and has been gradually applied for the theraputic purpose of knee osteoarthritis in recent years. This paper aimes to review the application of Tai Chi in the therapy of knee osteoarthritis from the origin and evolution of Tai Chi on the therapy of knee osteoarthritis to the current status of clinical research of Tai Chi intervention to knee osteoarthritis and its possible mechanism. This paper also summarizes the successes and deficiencies of previous studies which will provide design ideas for the future investigation of the application of Tai Chi in the therapy of knee osteoarthritis.